(untitled) (Chittagong University Journal of Biological Sciences, 2013)
Histopathological effect of three heavy metals- cadmium, chromium and mercury on the stomach tissue of catfish Magur, Clarias batrachus L. was studied under laboratory condition. Pathological symptoms due to metal stress showed significant damage of mucosal epithelium, hypertrophied epithelial cells with pyknotic nuclei and clear cytoplasm, separation of epithelium, separation of damaged digestive gland cells from the basement membrane, and vacuolation and rupture in submucosa and muscularis layer. Damages of the mucosal epithelial and gastric gland cells due to Cr treatment were significant while the epithelial hypertrophied cells undergone further deterioration due to Cd and Hg exposure. Blood vessels were hyperemic and necrosed in Cd and clumping of blood cells in the lamina propria beneath the mucosal epithelium in the fish exposed to Cr. DOI: http://dx.doi.org/10.3329/cujbs.v5i1.13365 The Chittagong Univ. J. B. Sci.,Vol. 5(1 &2):09-17, 2010